2007
DOI: 10.1071/zo06090
|View full text |Cite
|
Sign up to set email alerts
|

The extraordinary mating system of Zeus bugs (Heteroptera:Veliidae:Phoreticovelia sp.)

Abstract: However, the winged (macropterous) females lack these glands and the sexes are more similar in size (male length = 1.7 mm, female length = 1.7-2.05 mm: Polhemus and Polhemus 2000; Andersen and Weir 2001).Here, we report the first description of the habitat preferences and mating system of the two species of Australian Zeus Abstract. Wingless female Zeus bugs (genus: Phoreticovelia) produce a secretion from dorsal glands that males feed upon when riding on females. This unique form of sex-role-reversed nuptial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…in species of the genera Aquarius (29) and Rheumatobates (109) and even within populations of Gerris incognitus (98). Arnqvist et al (9) suggested that two female forms of Phoreticovelia bugs may lead to evolutionary divergence: wingless females carry and nourish diminutive males on their backs, while winged forms do not. McPeek et al (77, 78) inferred that male claspers and corresponding female structures evolved synchronously in Enallagma damselflies and are important for species recognition, but not under sexual selection.…”
Section: Behavioral Factorsmentioning
confidence: 99%
“…in species of the genera Aquarius (29) and Rheumatobates (109) and even within populations of Gerris incognitus (98). Arnqvist et al (9) suggested that two female forms of Phoreticovelia bugs may lead to evolutionary divergence: wingless females carry and nourish diminutive males on their backs, while winged forms do not. McPeek et al (77, 78) inferred that male claspers and corresponding female structures evolved synchronously in Enallagma damselflies and are important for species recognition, but not under sexual selection.…”
Section: Behavioral Factorsmentioning
confidence: 99%
“…It has been hypothesized that flightlessness of females per se constrains the mating success of females (Bell, 1982; Roff, 1990; Denno, 1994). Indirect support for this hypothesis is provided in a wing‐dimorphic insect whose wingless females (but not winged females) produce a dorsal secretion (nuptial gift) to attract and retain males for mating (Arnqvist et al., 2007), and also by the high incidence of mating failures in species with flightless females (Harshman & Futuyma, 1985; Sharov et al., 1995; Rhainds et al., 2009). Female flightlessness may have a particularly severe depressing effect on mating success when species exploit ephemeral or structurally complex habitats (Denno, 1994).…”
Section: A Priori Hypotheses Derived From Theoretical Studiesmentioning
confidence: 99%
“…Random mating encounters and low female mating success, particularly in sparse populations, have been hypothesized to lead to the evolution of adaptations enhancing mating success (Mosimann, 1958; Fauvergue et al., 1995; South & Kenward, 2001; Jonsson et al., 2003; Pearson et al., 2004). Females have indeed evolved extravagant physiological adaptations (Funk & Tallamy, 2000; Arnqvist et al., 2007; Kaufman, 2007) and a set of behaviours to increase their probability of mating, ranging from active foraging for mates (Wickman, 1986; Kaitala & Wiklund, 1994; Mendoza‐Cuenca & Maćias‐Ordóñez, 2009), aggressive interactions among conspecifics for access to males (Lynam et al., 1992; Papadopoulos et al., 2009), and selection of habitats most suitable for mate attraction (Shields, 1967; Scott, 1970; Rhainds et al., 1995a,b; Rhainds & Sadof, 2009). Females have further evolved covert behavioural adaptations to ensure that they mate at least once, e.g., indiscriminate mate choice of virgin females compared with mated females (Svensson et al., 1998; Kokko & Mappes, 2005; Peretti & Carrera, 2005; Kumano et al., 2009).…”
Section: A Priori Hypotheses Derived From Theoretical Studiesmentioning
confidence: 99%
“…The semi-aquatic Zeus bug, Phoreticovelia disparata, is extremely sexually size dimorphic (Andersen and Weir 2001). The smaller adult males ride on the back of females (using their legs to secure and maintain a position) and this pre-and post-mating association may last several days (Arnqvist et al 2007). The operational sex ratio is typically male biased (Arnqvist et al 2007).…”
Section: Introductionmentioning
confidence: 99%